Effect of rosiglitazone, metformin, and glyburide on bone biomarkers in patients with type 2 diabetes. - Zinman, B; Haffner, S; Herman, W; Holman, R; Lachin, J; Kravitz, BG; Paul, G; Jones, N; Aftring, R; Viberti, G; Kahn, SE (2010)
CONTEXT: An increase in bone fractures has been observed in women taking thiazolidinediones. OBJECTIVE: The objective of the study was to examine whether changes in circulating bone biomarkers provide insight into the underlying mechanisms responsible for the increase in bone fractures in female participants randomized to rosiglitazone in A Diabetes Outcome Progression Trial (ADOPT). RESEARCH DESIGN AND METHODS: Paired stored baseline and 12-month serum samples were available from 1605 participants (689 women, 916 men) in ADOPT, a long-term clinical trial comparing the effects of rosiglitazone, glyburide, and metformin on glycemic control in patients with type 2 diabetes. RESULTS: This subset was well matched to the total ADOPT study population. In women a marker of osteoclast activity, C-terminal telopeptide (for type 1 collagen), increased by 6.1% with rosiglitazone compared with reductions of 1.3% (P = 0.03 vs. rosiglitazone) and 3.3% (P = 0.002 vs. rosiglitazone) with metformin and glyburide, respectively. In men, C-terminal telopeptide was unchanged on rosiglitazone (-1.0%) and fell on metformin (-12.7%; P < 0.001) and glyburide (-4.3%, P = NS). Markers of osteoblast activity, procollagen type 1 N-propeptide (P1NP) and bone alkaline phosphatase, were reduced for women and men in almost all treatment groups, with the greatest changes in the metformin group (P1NP in females, -14.4%; P1NP in males, -19.3%), intermediate for rosiglitazone (P1NP in females, -4.4%; P1NP in males, -14.4%), and smallest for glyburide (P1NP in males, +0.2%; bone alkaline phosphatase in females, -11.6%). CONCLUSIONS: Commonly measured bone biomarkers suggest that changes in bone resorption may be partly responsible for the increased risk of fracture in women taking thiazolidinediones.